Detachable Speech: Artistic Expression, Same-Sex Weddings, and the First Amendment - Szynol, Paul (The Columbia Journal of Law & the Arts, 2025)
In the last decade, courts have consistently upheld objections to public accommodation laws that would obligate unwilling vendors to provide services for same-sex weddings. At the heart of these disputes is the claim that, when they are required to provide wedding services to same-sex couples, vendors who oppose same-sex marriage are unconstitutionally forced to endorse them. These cases typically classify wedding content, such as photography and wedding cakes, as a form of artistic, personal, and ideological speech that endorses same-sex weddings. In this paper, I argue that wedding content not only isn’t a form of endorsement, but that it is altogether devoid of political, religious, and ethical values attributable to the service provider. Rather than personal and ideological speech, wedding content is a form of speech that I call detachablespeech—that is, speech which is intentionally designed for adoption by another party, and, conversely, isn’t meant to convey the creator’s personal ideology. From advertisements and marketing materials to sitcoms and commissioned film screenplays, contentgenerators who work in creative industries routinely and voluntarily create expression that doesn’t reflect their personal values. Indeed, in some cases, detachable content—e.g., a greeting card or a sign meant for the front lawn—is fungible and arguably doesn’t even become speech until it’s adopted by another party. Similarly, wedding content is not designed to convey the service provider’s values any more than a greeting card reflects the manufacturer’s personal point of view. Wedding content, rather than ideological speech,is a form of speech widget produced to specification. The recognition that wedding content is not an endorsement substantially weakens the First Amendment challenge to public accommodation laws in connection with same-sex weddings.